Variations of the Superficial Middle Cerebral Vein: Classification Using Three-dimensional CT Angiography - Suzuki, Yasuhiro; Matsumoto, Kiyoshi (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Classification of variations of the superficial middle cerebral vein (SMCV) remains ambiguous. We propose a new classification system based on embryologic development for preoperative examination.METHODS: Three-dimensional CT angiography was used to evaluate 500 SMCVs (in 250 patients). The outflow vessels from the SMCV were classified into seven types on the basis of embryologic development. The 3D CT angiograms in axial stereoscopic and oblique views and multiple intensity projection images were evaluated by the same neurosurgeon on two occasions. Inconsistent interpretations were regarded as equivocal.RESULTS: Three-dimensional CT angiography clearly depicted the SMCV running along the lesser wing or the middle cranial fossa. However, the outflow vessel could not be confirmed as the sphenoparietal, cavernous, or emissary type in 39 (8%) of the sides. SMCVs running in the middle cranial fossa to join the transverse sinus or superior petrosal sinus were accurately identified. SMCVs were present in 456 sides: 62% entered the sphenoparietal sinus or the cavernous sinus and 12% joined the emissary vein. Nine vessels were the superior petrosal type, 10 the basal type, 12 the squamosal type, and 44 the undeveloped type.CONCLUSION: Three-dimensional CT angiography can depict the vessels and their anatomic relationship to the bone structure, allowing identification of the SMCV variant in individual patients. Preoperative planning for skull base surgery requires such information to reduce the invasiveness of the procedure. With the use of our classification system, 3D CT angiography can provide exact and practical information concerning the SMCV.